Impact of the rice variety,Uma (Mo16) on farmers - Neshva (Department of Agricultural Extension College of Horticulture, 2015)
Rice is the staple food of the people of Kerala, and traditionally, the cultivation of rice has occupied pride of place in the agrarian economy of the state. Palakkad and Alappuzha are the two major rice-producing districts of Kerala. About 600 varieties of rice were grown in the sprawling paddy fields of Kerala. One of the most popular rice varieties of Kerala is Uma (Mo.16) developed by the Rice Research Station, Moncompu of Kerala Agricultural University and it occupies more than 60 percent of the paddy cultivation area in Kuttanad region. The study intended to analyse the attributes of the rice variety, Uma (Mo16) vis-a-vis other rice varieties as perceived by farmers and to assess the socio economic impact of Uma on rice cultivating farmers. The study was confined to Kuttanad tract of Alappuzha. An ex-post facto research design was adopted for the study. Five padasekharams were selected through simple random sampling method, and from each padasekharam, 20 farmers cultivating the rice variety, Uma were selected, thus constituting a sample size of 100. A pretested structured interview schedule and PRA techniques were employed for data collection. The results revealed that tolerance to pests and diseases was ranked first with an index of 94.60 followed by non-lodging nature of plant (92.60), non-shattering nature of panicle (86.70), amenability to mechanisation (75.40), millers’ preference (49.60) and cooking quality (42.00). Varietal comparison of other rice varieties prevalent in Kuttanad area with ‘Uma’ using PRA technique revealed that ‘Uma’ was perceived as the superior variety with a score of 520.42 followed by Jyothi (443.95) and Prathyasa (418.72). Results of SWOC analysis done using PRA techniques, revealed that among the strengths, ‘high yield’ ranked first with an index of 98.80 followed by ‘tolerance against pest and disease incidence’ (96.00), ‘high grain weight’ (91.00), ‘high tillering capacity’ (89.00) and ‘high seed dormancy’ (85.2). However, low cooking quality (96.10) and less preference of the rice variety by millers (94.2) were emerged as the major weaknesses. It was, also found that all the respondents were continuously cultivating ‘Uma’ without any varietal shift. Majority (56 per cent) of the farmers had been continuously cultivating the rice variety, Uma for the past 15-17 years. With regard to the social impact on farmers, it was revealed that social participation has improved significantly. Similarly, information seeking behaviour has also increased positively, where as labour use has decreased significantly. However, there was no significant change in the communication behaviour of farmers. As regards economic impact, ‘annual income’, ‘family expenditure’, ‘savings’ and ‘asset creation’ of farmers have increased significantly after cultivation of the rice variety, Uma as compared to pre-Uma period. Indebtedness of farmers was also found to have decreased. Thus, the rice variety Uma could make a very promising impact on the socio- economic variables of farmers. Regarding comparative income advantage of Uma, it was found that this variety had an income advantage of Rs.38000/- per ha over the variety, Jyothi and Rs.95000/- per ha over local varieties. Thus, for a single puncha season, Uma had given an additional income of Rs.104.30 crores as compared to Jyothi and Rs.260.75 crores as compared to local varieties, in Kuttanad tract of Alappuzha alone. With regard to constraints faced by Kuttanad farmers, ‘non-availability of labour’ was ranked first with an index of 98.60 followed by ‘high cost of inputs’ like fertilizers and pesticides (89.60), ‘vagaries of weather and climatic conditions’ (81.20) and ‘non fixing of floor price on time’ (70.80